The National EcoBioTox Conference. The importance of ecotoxicology, bioindication, biodegradation in identifying and solving environmental problems in the era of the Anthropocene and climate change from the molecular to the landscape scale, Lodz 19–21.04.2023 : Księga abstraktów - zbiorowa, praca (Lodz University Press, 2023)
The EcoBioTox Conference is a continuation of the cyclical National Bioindication Conference, which was held from 2011 to 2021, in different cities. From 2023, we would like to invite you to participate in a new edition of the venue, connected with the location of the conference permanently in Lodz, and, first of all, with the extension of the subject matter to include the issues of degradation, biotransformation of pollutants, aspects relevant to the search for optimal solutions for improving the quality of the environment in the era of the Anthropocene and climate change. The aim of EcoBioTox is to promote the newest scientific achievements and to increase knowledge and competence through presentation of research results, discussion and exchange of experiences. Oral and poster presentations cover aspects of the use of a broad spectrum of bioindication tools in monitoring of the quality of the environment and human health from the molecular to the landscape scale. A second important element of the conference is the presentation of any biotechnological solutions and activities leading to biodegradation, bioremediation of pollutants, aspects relevant to the search for optimal nature-based solutions (NBS). The leading themes of the conference are: 1. The use of bioassays and biological methods for monitoring and assessment of environmental quality and estimation of environmental and health risks. 2. The use of microorganisms and molecular tools in ecotoxicological studies, including: mutagenicity and genotoxicity determination, enzyme and hormone activity determination, genetic markers for early warning systems. 3. Applications of bioindication systems in the practical analysis and toxicity assessment of wastewater, surface and groundwater, sediment and substances in the solid phase and in the air – challenges in times of anthropopression and climate change. 4. Biodegradation and detoxification of pollutants of anthropogenic and natural origin. 5. Bioremediation of contaminated water and soil environments. 6. Administrative and legal aspects of the use of bioindication and bioassay methods. 7. Risk assessment procedures in environmental management.